Leveling with friends: Social networks and indian farmers’ demand for agricultural custom hire services - Magnan, Nicholas; Spielman, David J.; Lybbert, Travis J.; Gulati, Kajal (International Food Policy Research Institute, 2013)
This research was undertaken to understand how information about a new agricultural technology is transmitted through social networks, and what effect information gained through social networks has on technology demand at the household level. The technology in question is laser land leveling (LLL)-a resource-conserving technology-which we introduced in eastern Uttar Pradesh, India as part of the study. Using an experimental auction, we obtain farmers’ willingness-to-pay for the technology and identify potential adopters. We then randomly select half of these farmers to actually receive LLL services on their land, creating random variation in the number of adopters in each farmer’s social network. We conduct a second auction one year later with the same sample of farmers and estimate network effects on farmers’ updated willingness-to-pay. Four main results emerge: First, exposure to LLL through networks occurs primarily through visits to adopting farmers’ fields. Second, having a first-generation adopter in a farmer’s network increases the farmer’s valuation of LLL by nearly 30 percent on average. Third, the network effects on demand are importantly conditioned on benefits associated with LLL, which implies that learning-rather than mimicry-is driving increases in demand. Fourth, network effects are strongest between poor farmers.